Climate-responsive strategies of vernacular architecture in Albania and Portugal - Fernandes, Jorge Emanuel Pereira (2017)
The influence of climate on vernacular architecture is widely recognised. In the case of the Mediterranean Sea, its influence on climate ranges a wide variety of territories and cultures. Therefore, it is relevant to study how the climatic factor has modelled vernacular architecture in those territories and if there are common features. In this exploratory study are qualitatively compared the climate-responsive strategies of vernacular architecture from two countries located on opposite sides of the Mediterranean basin, namely, Portugal and Albania. The pragmatism of these strategies, developed on the need of adaptation to a specific climate and territory, may con-tribute to reduce energy consumption and waste. The study allowed showing points of similarity between strategies used in the two countries and, understanding how these strategies influence indoor comfort conditions. The results of the study can be used to develop and integrate these strategies in the current construction context, contributing to its sustainability.